2002
DOI: 10.1046/j.1469-8137.2002.00380.x
|View full text |Cite
|
Sign up to set email alerts
|

Within‐stem variation of respiration in Pseudotsuga menziesii (Douglas‐fir) trees

Abstract: Summary• A technique for measuring in vitro respiration was investigated to understand why rates were higher than those reported in vivo and to elucidate trends within mature Pseudotsuga menziesii (Douglas-fir) trees.• Extracted increment cores were divided into 3 -4 radial depths and a gas chromatograph was used to compare respiration rates radially and vertically within stems.• Respiration of inner bark was 2-3 times greater than sapwood, and 50 -70% higher in outer than inner sapwood. Inner bark and outer s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 39 publications
4
37
0
Order By: Relevance
“…The patterns of increasing respiratory potential from the sapwood/heartwood boundary to the inner bark identified within the ten different tree species from the central Cascades, Oregon were similar to those in Pinus ponderosa and Pseudotusga menziesii (Pruyn et al 2002a(Pruyn et al , 2002b. Increased respiratory activity of the inner bark and outer sapwood rings of stems may be related to their ray parenchyma cells being more involved in supporting growth and secondary wall formation in the cambial zone (Goodwin and Goddard 1940) as compared to the inner rings where the roles of parenchyma may be more storage oriented (Dickson 1991).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…The patterns of increasing respiratory potential from the sapwood/heartwood boundary to the inner bark identified within the ten different tree species from the central Cascades, Oregon were similar to those in Pinus ponderosa and Pseudotusga menziesii (Pruyn et al 2002a(Pruyn et al , 2002b. Increased respiratory activity of the inner bark and outer sapwood rings of stems may be related to their ray parenchyma cells being more involved in supporting growth and secondary wall formation in the cambial zone (Goodwin and Goddard 1940) as compared to the inner rings where the roles of parenchyma may be more storage oriented (Dickson 1991).…”
Section: Discussionmentioning
confidence: 75%
“…Immediately prior to measurement, core segments were re-weighed and placed in 25 ml vials, which were then sealed with gas-tight rubber septa. Respiration of core samples was measured using a previously developed protocol, which was proven reliable and repeatable (Pruyn et al 2002b), and free of potential artifacts from measurement conditions (e.g. oxygen depletion in the vials, or non-sapwood parenchyma cell sources of CO 2 production).…”
Section: Respiratory Measurements-laboratory Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we scaled up rates of F s at DBH to the entire stem, while it has been reported that specific rates of respiration vary along the stem (e.g. Damesin et al, 2002;Pruyn et al, 2002). Second, in April, sapwood-based F s rates were negatively correlated with stem diameter -suggesting that smaller and perhaps younger stems had a higher cambial activity than larger ones (Bosc et al, 2003).…”
Section: Stand-level Stem C0 2 Effluxmentioning
confidence: 99%
“…The rapid increase in CO 2 efflux observed after tissues are excised or injured is likely the result of rapid diffusion of CO 2 from the xylem, rather than an actual increase in the rate of respiration of the wounded tissues (Teskey et al, 2005). It was reported that 15%-75% of CO 2 moved upward with the sap flow during daytime, while 100% respired CO 2 was released into the ambient atmosphere via the bark at night when the stem sap flow ceased (McGuire et al, 2004;Bowman et al, 2005;Pruyn et al, 2002;. The site of the xylem in the vicinity of the cambium layer contains a large amount of CO 2 at an evidently higher concentration than the surrounding ambient atmosphere, and sometimes it is even 3 times higher (Eklund, 1990;Levy et al, 1999;McGuire et al, 2004).…”
Section: Stem Respiration and Forest Managementmentioning
confidence: 99%